A series of soluble thieno-fused coronene nanoribbons of precise lengths [data] - Yang, Xuan; Elbert, Sven; Rominger, Frank; Mastalerz, Michael (Universität, 2022)
Among graphene nanoribbons (GNRs), reports on coronene-based GNRs were very rare, despite the unique optoelectronic properties of coronene. Herein,...